การชะละลายตะกั่วจากพลอยทับทิมที่ผ่านการเผาด้วยแก้วตะกั่ว - พัชรินทร์ เหล็กกล้า (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Nowadays, gem ruby enhancement industry in Thailand has applied heat treatment with lead glass additive to improve transparency and beautifulness of stones. However, this process has been criticized by academics such as environmentalists and gemologists, entrepreneurs as well as user, particularly on safety of jewelry wearing. It has impacted to gem exportation of the country. Therefore, this research was conducted to answer the following aspects. (1) The lead concentration leached from ruby by Three-Stage Sequential Extraction Procedure (BCR three stages) including exchangeable, reducible and oxidisable. In addition, BCR procedure was designed into three series: series 1, the common steps from BCR 1 to 2 and 3; series 2, modified steps from BCR 2 to 3 and 1;series 3,modified steps from BCR 3 to 1 and 2. (2)The concentration leached from ruby by EN71-3 method which is the standard test of lead concentration in children toys of European Union. (3) The concentration of total lead in ruby using modified standard method for lead in products for children, including jewelry (modified CPSC-CH-E1001-8.1, 2010). Ruby samples were collected from factories in Chanthaburi. These samples were declared in two types, including classical heated rubies (old heating technique) from 7 factories and lead glass heated rubies (new heating technique) from 5 factories.As the results of classical heated ruby samples, series 1 (accumulated BCR 1, 2 and 3) yielded lead concentrations of 13.0 - 126.3 mg/kg; series 2 (accumulated BCR 2, 3 and 1) yielded lead concentrations of lower than detection limit to 120.5 mg/kg; series 3 (accumulated BCR 3, 1 and 2) showed lead concentrations of 20.7- 292.7 mg/kg. Regarding to lead glass heated ruby samples, series 1 (accumulated BCR 1, 2 and 3) yielded lead concentration of 1342.9 - 7526.7 mg/kg; series 2 (accumulated BCR 2, 3 and 1) yielded lead concentrations of 207.6 - 4768.6 mg/kg; series 3 (accumulated BCR 3, 1 and 2) yielded lead concentrations of 99.8 - 5046.1 mg/kg. Moreover, the gemological appearance of ruby after leaching step was found to be agreed well with lead leaching off for each step.In addition, the results of EN71-3 method yielded concentrations of lead leached from lead glass treated ruby samples of 134.9 -1397.6 mg/kg that are obviously higher than standard content (< 90 mg/kg). Furthermore, the results of modified CPSC showed concentrations of lead leached from same samples of 1353.4 - 8668.2 mg/kg that are enormously higher than standard content (< 90 mg/kg).